Building the Infrastructure of Anti-Trafficking, Part II: Why measurement matters - David, Fiona (Anti-trafficking review, 2017)
Having worked on human trafficking issues since the late 1990s, I have been fortunate to observe the rapid development of the infrastructure necessary to respond to these crimes. In 1999, a time of much concern about ‘mail order brides’ and debates about the differences between human trafficking and smuggling, I published a report noting that:In Australia, as in other countries of the world, limited evidence is available about the nature and incidence of trafficking in persons. There is some anecdotal evidence of trafficking activity occurring in various industries, including hospitality, manufacturing, and agriculture. The sector that has received the most media attention, however, is the sex industry